Efectos de combinación de insecticidas sobre el control de insectos plagas en el cultivo de frejol caupí (Vigna unguiculata L.) - Cobeña Sánchez, Jordán Antonio (2022)
The objective of the research was to evaluate the effect of insecticides on the control of insect pests on a cowpea crop (Vigna unguiculata L.) at ESPAM MFL. The experiment was performed on the conventional field in the Agricultural Engineering Department of ESPAM-MFL, located in El Limón, Bolívar, Manabí. A single-factorial (a+1), randomized complete block design (a+1) was used, with four replicates, with a total of 24 experimental units. The treatments evaluated were T1: Imidacloprid (15dds), Spinetoram (30 dds), Imidacloprid (45 dds, T2: Thiamethoxam (15dds), Spinetoram (30 dds), Thiamethoxam (45dds T3: Lamdacihalothrin (15 dds), Spinetoram (30 dds), Lamdacihalothrin (45 dds), T4: Imidacloprid (15dds), Lamdacihalothrin (30 dds), Imidacloprid (45 dds), T5: Thiametoxam (15dds), Lamdacihalothrin (30 dds), Thiametoxam (45dds) and T6: control treatment. The analysis of variance showed that treatments T2 and T5 showed the lowest incidence of Empoasca spp., and they were also the treatments with the highest efficiency for insect reduction; treatment T2 registered the highest averages in most of the productive variables evaluated, with a 33% difference in yield compared to when no insecticides were applied; it also generated the highest net profit and the best marginal rate of return